Mental Transdiplinarity: Observe, Participate, Know and Act, a Grounded Theory Biographic - Tietsche , Claudia (Cadernos de Educação Tecnologia e Sociedade, 2022)
The objective is, through the processes of observing, participating, knowing and acting, to reflect on the freedom and limitations of mental transdisciplinarity in the development of a grounded theory. This written material is organized into four sections: the first unravels what I want with the mental transdisciplinary nomenclature, the second dialogues with ethnographic participant observation, the third relates to action research and the last characterizes, from the previous ones, a biographical grounded theory. A challenging advisor, a challenging banker, provocative authors are always sowers of questioning, of movement, so that the new has the opportunity to emerge in an active process and the field of choices is made possible for us to cultivate it with fertile seeds, for others to savor of their fruits, and, if they consider it prudent, reuse the seeds that these fruits keep.